Upper ocean mixing, surface heat fluxes, and heat content variability in the upper 150 m during Hurricane Laura (2020) - Senam K. Tsei; Stephan D. Howden; Arne R. Diercks; Karthik Balaguru; Matthieu Le Hénaff; Jun A. Zhang; Iam-Fei Pun; Kevin M. Martin (Frontiers in Marine Science, 2026)
This study integrates thermistor observations, hurricane glider measurements, and model-derived temperatures to examine the oceanic processes influencing Hurricane Laura’s rapid intensification, the role of the preexisting warm mixed layer at Stone Mooring (StM) in modulating cooling of the mixed layer, and the processes governing mixed layer heat evolution during and after storm. Prior to the storm’s passage, StM featured a 31°C warm mixed layer and elevated heat content (60–80 kJ/cm 2 ), which strongly preconditioned the upper ocean. Thermistor data showed that Hurricane Laura produced a mixed layer cooling of 1.2°C on 26 August, compared with a model-estimated cooling of −1.04°C. A 1D shear-driven mixed layer model experiment indicates that, without the warm preexisting mixed layer, temperatures could have cooled down to 28.53°C, supporting the hypothesis that thermal structures associated with Loop Current warm core eddies rarely experience substantial cooling during hurricane passage. We also show that relatively small surface heat fluxes (5.04 kJ/cm 2 ) sustained Hurricane Laura during intensification at StM. Mixed layer heat budget analysis shows that entrainment and surface heat fluxes were the primary drivers of the observed temperature tendency. These results improve understanding of upper ocean processes and demonstrate that observations from StM provide valuable constraints for operational hurricane models in the Gulf of Mexico.

Impact of local rivers on coastal acidification - Allison M. Savoie; Amy Moody; Melissa Gilbert; Kevin S. Dillon; Stephan D. Howden; Alan M. Shiller; Christopher T. Hayes (Limnology and Oceanography, 2022)
Coastal ecosystems are highly dynamic areas for carbon cycling and are likely to be negatively impacted by increasing ocean acidification. This research focused on dissolved inorganic carbon (DIC) and total alkalinity (TA) in the Mississippi Sound to understand the influence of local rivers on coastal acidification. This area receives large fluxes of freshwater from local rivers, in addition to episodic inputs from the Mississippi River through a human‐built diversion, the Bonnet Carré Spillway. Sites in the Sound were sampled monthly from August 2018 to November 2019 and weekly from June to August 2019 in response to an extended spillway opening. Prior to the 2019 spillway opening, the contribution of the local, lower alkalinity rivers to the Sound may have left the study area more susceptible to coastal acidification during winter months, with aragonite saturation states (Ω ar ) 2 concentrations in subsurface waters. Increased Mississippi River input could represent a new normal in the Sound's hydrography during spring and summer months. The spillway has been utilized more frequently over the last two decades due to increasing precipitation in the Mississippi River watershed, which is primarily associated with climate change. Future increases in freshwater discharge and the associated declines in salinity, dissolved oxygen, and Ω ar in the Sound will likely be detrimental to oyster stocks and the resilience of similar ecosystems to coastal acidification.